2019
DOI: 10.3390/ijms20246284
|View full text |Cite
|
Sign up to set email alerts
|

Exercise as A Potential Therapeutic Target for Diabetic Cardiomyopathy: Insight into the Underlying Mechanisms

Abstract: Diabetes mellitus is associated with cardiovascular, ophthalmic, and renal comorbidities. Among these, diabetic cardiomyopathy (DCM) causes the most severe symptoms and is considered to be a major health problem worldwide. Exercise is widely known as an effective strategy for the prevention and treatment of many chronic diseases. Importantly, the onset of complications arising due to diabetes can be delayed or even prevented by exercise. Regular exercise is reported to have positive effects on diabetes mellitu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 144 publications
(186 reference statements)
1
24
0
Order By: Relevance
“…Exercise reduces the production of ROS, and reduces oxidative stress damage, additionally exercise upregulates the expression and function of anti-oxidants enzymes superoxide dismutase, glutathione peroxidase and catalase ( Seo et al, 2019 ), and “exerkines” ( Yu et al, 2017 ). As a result of the above, exercise in diabetic patients; reduces overall cardiovascular disease burden, improves endothelial function, improves indices of cardiac dysfunction, reduces overall hyperglycemic time and reduces the long term index of poor glucose control (glycated hemoglobin, HbA1C) ( Seo et al, 2019 ). Exercise is simple intervention, which reduces cardiovascular morbidity and mortality and positively correlates with beneficial health outcomes as they pertain to diabetes and other chronic illnesses.…”
Section: Exercisementioning
confidence: 99%
“…Exercise reduces the production of ROS, and reduces oxidative stress damage, additionally exercise upregulates the expression and function of anti-oxidants enzymes superoxide dismutase, glutathione peroxidase and catalase ( Seo et al, 2019 ), and “exerkines” ( Yu et al, 2017 ). As a result of the above, exercise in diabetic patients; reduces overall cardiovascular disease burden, improves endothelial function, improves indices of cardiac dysfunction, reduces overall hyperglycemic time and reduces the long term index of poor glucose control (glycated hemoglobin, HbA1C) ( Seo et al, 2019 ). Exercise is simple intervention, which reduces cardiovascular morbidity and mortality and positively correlates with beneficial health outcomes as they pertain to diabetes and other chronic illnesses.…”
Section: Exercisementioning
confidence: 99%
“…42 It is broadly recognized as an effective strategy for the prevention and management of many chronic diseases. 43 Moderate exercise following Roux-en-Y gastric bypass surgery was found to provide additional improvements in insulin sensitivity, glucose effectiveness, and cardiorespiratory fitness for obese individuals. 44 The effects of exercise and leisure time PA have been extended from prevention to management of several components of metabolic syndrome and also for the mood and quality-of-life.…”
Section: Physical Activitymentioning
confidence: 99%
“…70 Exercise is used for the prevention, 71 and treatment of T2DM [72][73][74][75][76][77][78] by improving glycemic control. 43,[79][80][81][82][83][84][85][86] It is a comprehensive element of diabetes management. 87,88 A randomized trial has reported that exercise performed for 30 minutes after meal eating may provide better improvements in glycemic control for people with T2DM.…”
Section: Management Of T2dmmentioning
confidence: 99%
“…Exercise has been proposed to elicit beneficial effects through multiple mechanisms, as recently reviewed ( Hafstad, Boardman & Aasum, 2015 ; Seo et al, 2019 ) and indicated in Fig. 4 .…”
Section: Resultsmentioning
confidence: 99%